Analisis Volatilitas Return Saham Terhadap Risiko Sistematis Dimasa Pandemik Covid-19 pada Saham LQ 45 - Solekha, Yasmin Afnan; Winarto, Wahid Wachyu Adi (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2020)
The Covid-19 pandemic has had a very big impact. All parts of the world are making efforts to prevent the spread of this virus, decisions to lockdown, quarantine areas, or PSBB. Which resulted in delays in the economy and financial markets. Domestic and foreign investors dispose of their funds in order to prevent risks. JCI recorded that in February the price index fell to a level of 3938. Stock prices that tend to be unstable will affect the volatility of returns (fluctuations in the level of returns that will be obtained by investors) and systematic risk (deviations from the outcome of their expected returns). Therefore, a research was conducted to examine the stocks that had been randomly selected on LQ45, namely LPPF, ASII, ANTM, TLKM, and BBRI for the period November 2019-October 2020 through quantitative methods using e views 10, where all data was obtained by secondary literature study. From the stock price, there is a very sharp stock return volatility. The lowest average stock return volatility is in ASII shares valued at -0.006264. Meanwhile, the highest average volatility is ANTM stocks 0.053972. The sharp volatility shows that all five stocks have risks. LPPF, ASII, ANTM, and BBRI stocks have a beta value (risk)> 1 which means the stock is risky. The expected return is higher than the market return. This is also in line with the standard deviation of the LPPF which scores the highest. Meanwhile, TLKM shares have a beta value <1 or the volatility of stock returns is below the market return. This means that stocks have little risk, the expected return is lower than the market return.